Impact of Biotic Disturbances on Vegetation and Litter Accumulation in Alpine Meadows of Nandadevi Biosphere Reserve - Singh, Sanjeeva K.; Rai, J. P. N. (Indian Forester, 2005)
The present investigation reports on the phytosociological attributes of plant species encountered and changes in litter accumulation in alpine meadows exposed to a gradient of biotic pressures in buffer zone of Nanda Devi Biosphere Reserve. Danthonia cachemyriana showed maximum IVI in the moderately disturbed site whilst Kobressia duthiea in the intensively disturbed site. Maximum litter accumulation was recorded in the moderately disturbed site in October whilst minimum in the intensively disturbed site during August. On contrary to the undisturbed meadow, in the intensively disturbed meadow total litter production was contributed minimum by the grasses-more palatable plants.